(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
The article presents an analysis of priority areas for the development of the service sector in Uzbekistan. From the point of view of introducing new types of services into the services market of Uzbekistan, changing consumer needs and increasing requirements for the quality and speed of services provided, it is necessary to create an economic system that is flexible for In accordance with changes of time, making scientifically based decisions in the formation of targeted and targeted development programs and new strategies, the development of a unique national approach taking into account advanced international standards becomes the main task in the implementation of macroeconomic and statistical policies.